Annotated catalogue of type specimens of flatfishes (Osteichthyes: Pleuronectiformes) in the Zoological Institute, St. Petersburg, Russia - Voronina, Elena P.; Volkova, Galina A. (Zootaxa, 2019)
A complete catalogue is provided for the type specimens of flatfishes curated in the ichthyological collection of the Zoological Institute, St. Petersburg. The collection contains a total of 138 type specimens, representing 25 species and one subspecies of eight different flatfish families. The catalogue includes: photographs of type specimens, radiographs of holotypes or largest syntypes, number of specimens, original sampling data (locality, coordinates, depth, collection date and collector), and select morphometric characters for each specimen.